13O years of fiscal vulnerabilities and currency crashes in advanced economies - Fratzscher, Marcel (2011)
Investigates the empirical link between fiscal vulnerabilities and currency crashes in advanced economies. Reports that evidence finds that crashes depend more on prospective fiscal deficits than on actual ones, and more on the composition of public debt than on its level.